Determinants of rheumatic heart disease: findings from qualitative research approach - Ajeng, Rudy Ngau; Rahman, Mohammod Mizanur; Said, Asri Bin; Adenan, Abang Safuan Bin; Ameenudeen, Mohamed; Kim Choo, Greta Miranda Goh; Siddiq, Muhammad; Gahamat, Mohamed Faiz (Indonesian Pediatric Society, 2023)
Background Rheumatic heart disease (RHD) is an autoimmune heart disease following unresolved or untreated Acute Rheumatic Fever (ARF), which results in irreversible valve damage and heart failure. Strategies for managing RHD could be planned to understand the disease determinants in local settings. Objective To explore the determinants of RHD among the family with an RHD case. Methods The study was a qualitative design using a grounded theory approach after in-depth interviews with respondents from families with RHD patients. Analysis was conducted after the scripts were finalized. Initial, intermediate, and advanced codings were performed. Ten respondents agreed to participate and completed the qualitative data collection process. Results The analysis yielded two theme categories of what could have led to RHD among respondents due to internal and external causes. Internal causes were considered factors that could be managed or manipulated to improve an individual and family’s capacity. In contrast, external causes were considered factors that could not be managed or manipulated to improve an individual’s capacity or family. Therefore, these factors were considered beyond their control. Conclusion This study explored RHD determinants according to the patients’ and their families’ perspectives. A holistic approach can be applied to managing RHD by considering these factors.